2018
DOI: 10.3390/w10030256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Level Increase on Phytoplankton Assemblages in a Drinking Water Reservoir

Abstract: Excessive water level fluctuation may affect physico-chemical characteristics, and consequently ecosystem function, in lakes and reservoirs. In this study, we assessed the changes of phytoplankton assemblages in response to water level increase in the Danjiangkou Reservoir, one of the largest drinking water reservoirs in Asia. The water level increased from a low of 137 m to 161 m in 2014 as a part of the South-North Water Diversion Project. Phytoplankton assemblages were sampled four times per year before, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…Environmental factors such as nutrients, light, and hydrodynamic conditions [1][2][3] impact the general composition of phytoplankton through their synergistic effects. High concentrations of nutrients are critical for the formation of algal blooms but are not always the determining factor [4].…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors such as nutrients, light, and hydrodynamic conditions [1][2][3] impact the general composition of phytoplankton through their synergistic effects. High concentrations of nutrients are critical for the formation of algal blooms but are not always the determining factor [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that water level fluctuations have a great influence on the phytoplankton composition [44]. Phytoplankton compositional changes may greatly reflect environmental changes, such as changes in hydrodynamics mediated by water level increases [45]. Therefore, long-term monitoring of the phytoplankton evolution in the AHR was conducted while artificially controlling of the water levels.…”
Section: Species Composition Of the Phytoplanktonmentioning
confidence: 99%
“…Al igual que lo registrado en el embalse Punchiná, en San Lorenzo el fitoplancton no fue afectado por las temporadas climáticas de sequía y lluvia, pero cuando estas últimas se incrementaron en gran magnitud durante el fenómeno de La Niña, la estructura fitoplanctónica sufrió alteraciones significativas y disminuyó su número de individuos (glm ajustado a gamma inverso; densidad aic = 1107,6; p = 6,97e -7 ), de taxones y su diversidad en general (figura 124). En embalses colombianos y del trópico en general existen muy pocos estudios sobre los efectos de los fenómenos enso sobre la comunidad algal (Hernández-Roa, 2014;Pineda et al, 2019); sin embargo, en otros sistemas se ha reportado también la disminución de la diversidad durante las fuertes lluvias causadas por el fenómeno de La Niña (Doan-Nhu et al, 2016) y un descenso de la biomasa algal por el incremento del nivel del agua (Pan et al, 2018), debido al efecto de dilución.…”
Section: Fitoplanctonunclassified